The labor/land ratio and India's caste system - Harriet Duleep (Institute for the Study of Labor (IZA), 2012)
This paper proposes that India's caste system and involuntary labor were joint responses by a nonworking landowning class to a low labor/land ratio in which the rules of the caste system supported the institution of involuntary labor. The hypothesis is tested in two ways: longitudinally, with data from ancient religious texts, and cross-sectionally, with twentieth-century statistics on regional population/land ratios linked to anthropological measures of caste-system rigidity. Both the longitudinal and cross-sectional evidence suggest that the labor/land ratio affected the caste system's development, persistence, and rigidity over time and across regions of India.
Keywords: J47; J1; J30; N3; Z13; 330; labor-to-land ratio; population; involuntary labor; immobility; value of life; marginal product of labor; market wage; Soziale Schicht; Sklaverei; Arbeitskräfte; Boden; Faktorintensität; Eigentümerstruktur; Arbeitsproduktivität; Sozialgeschichte; Indien